1990
DOI: 10.2307/1368241
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of the Wood Thrush in Southern Veracruz, Mexico

Abstract: Abstract. The Wood Thrush Hylocichla mustelina (Muscicapidae: Turdinae) was studied on wintering grounds in the rainforest of southern Veracruz, Mexico, using mist netting, radiotelemetry, and field observation. Data were collected during three boreal winters (primarily November-March), and 46 individuals received transmitters. All sex and age classes were present, but difficulties in aging and sexing did not allow accurate determination of proportions. Telemetry showed two types of spatial use: "sedentary" (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 42 publications
5
62
0
3
Order By: Relevance
“…REVI winter in mixed-species flocks and are not territorial (60,61); thus, their arrival time may be less constrained, allowing them to wait for more favorable conditions and avoid the risks of crossing a large body of water. Conversely, SWTH and WOTH defend winter territories (62,63), and the benefits of taking quicker, more direct routes to acquire higher quality territories may outweigh the potential risk of encountering inclement weather over water. Additionally, although all three species are known to consume fruit during fall migration and on the wintering grounds, REVIs typically glean insectivorous prey from broad-leaved canopy foliage (48,64,65), whereas Swainson's Thrush and Wood Thrush forage on the ground and in low vegetation (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…REVI winter in mixed-species flocks and are not territorial (60,61); thus, their arrival time may be less constrained, allowing them to wait for more favorable conditions and avoid the risks of crossing a large body of water. Conversely, SWTH and WOTH defend winter territories (62,63), and the benefits of taking quicker, more direct routes to acquire higher quality territories may outweigh the potential risk of encountering inclement weather over water. Additionally, although all three species are known to consume fruit during fall migration and on the wintering grounds, REVIs typically glean insectivorous prey from broad-leaved canopy foliage (48,64,65), whereas Swainson's Thrush and Wood Thrush forage on the ground and in low vegetation (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Turdus grayi was relatively abundant in the continuous forest (CF) and large forest fragment (F40), while H. mustelina was abundant in all sites (CF,F40,and F3). Different studies of the bird community conducted at Los Tuxtlas have reported that T. grayi and H. mustelina are also able to use forest edges, forest and riparian remnants, living fences, and isolated trees (Winker et al 1990;Estrada et al 2000;Graham and Blake 2001;Graham et al 2002), suggesting that these species are not strongly affected by forest fragmentation because they can move among different landscape patches. The ability of the most effective species to move among landscapes patches suggests that they could disperse D. arboreus seeds to different sites, eventually contributing to seedling recruitment and gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although their presence in human modified habitats may provide a first-order indication of their suitability for these species, survival rates of some migrants can be lower in human modified habitats due to predation (Rappole et al 1989). Thus, the existence of these species in modified habitats might signify that preferred habitats are saturated, resulting in the exclusion of some individuals from preferred habitats (Winker et al 1990;Marra et al 1993). Furthermore, it is likely that we underestimated the differences between primary forest and other habitats for both migrants and residents because mist nets sample decreasing amounts of the avifauna [migrant as well as resident] with increasing canopy height (Rappole et al 1998).…”
Section: Differences In Richness Among Habitatsmentioning
confidence: 99%